Comorbid Diagnosis of Psychotic Disorders in Borderline Personality Disorder: Prevalence and Influence on Outcome - Slotema, C. W.; Blom, Jan D.; Niemantsverdriet, Marieke B. A.; Deen, Mathijs; Sommer, Iris E. C. (Frontiers in Psychiatry, 2018)
Background: A diagnosis of psychotic disorder is traditionally considered incompatible with borderline personality disorder (BPD), even though patients sometimes fulfill the diagnostic criteria for both disorders. How often this happens is barely known, as is the influence of comorbid psychotic disorders on the outcome of BPD. Since studies on isolated auditory verbal hallucinations in patients with BPD indicate that these perceptual symptoms have severe consequences, and are associated with suicidal behavior and hospitalization, patients with comorbid psychotic disorders are unlikely to fare better. Objective: To examine the point prevalence of psychotic disorders in patients with BPD, their association with the outcome of BPD, and their predictive value for outcome. Methods: In a cross-sectional design, 84 female outpatients diagnosed with BPD were interviewed with the aid of the MINI-International Neuropsychiatric Interview to establish the point prevalence of comorbid psychotic and other comorbid disorders. After termination of their treatment at a specialized outpatient clinic, the type of referral was considered to be a ‘good ‘outcome when they were referred to their general practitioner or to basic psychiatric care for noncomplex patients, and a ‘poor’ outcome when referred to a specialized psychiatric department or to a psychiatric district team for patients with severe psychiatric disorders. Results: Psychotic disorders were present in 38% of the patients with BPD. With a prevalence of 20%, psychotic disorder not otherwise specified (NOS) was the most common subtype; the least common types were schizophrenia (2%), substance-induced psychotic disorder (2%), and brief psychotic disorder (1%). Among six types of comorbid disorders, only psychotic disorders were associated with a poor outcome; they were also predictors for a poor outcome, along with comorbid mood disorders, eating disorders, and somatoform disorders, as well as the severity of BPD, and, counterintuitively, more years of education. Conclusion: Psychotic disorders, notably of the psychotic disorder NOS subtype, are common among patients with BPD, and their presence is associated with a poor outcome. This implies that adequate diagnosis and treatment of both disorders is warranted in this subgroup with a dual diagnosis.